PKM PALAPA (Pembuatan Aplikasi Laporan Perkembangan Anak) Kelompok A Pada TK An Shal Kecamatan Kamal Kabupaten Bangkalan - Rica Wijayanti (JAST : Jurnal Aplikasi Sains dan Teknologi, 2018)
Kindergarten is one of the levels of education that began to be promoted by the government before going through the elementary school level. Based on preliminary observations made by service providers at the AN-SHAL Kindergarten, it appears that some children have developed according to the stage of development of their children, but some children are far behind. This is a problem at the school. Children whose development is still below average have lazy tendencies when given assignments both at school and at home. One of the efforts made by the teacher at the AN-SHAL Kindergarten was to make a letter to parents whose children had problems. However, the effort seemed to be a waste because most of their parents could not attend and those present were the caregivers who were in charge of delivering and picking up the children. This difficulty is felt by teachers because most parents of their students are busy working. As a result, the problem of children who are lazy to do tasks continues. The solution given in this community service program is to make an android child development report application. The method used is using the development method. The making of this application was developed from a report on child development in the form of a manual into an application with the help of an android developer kit application and java SE. The results of this service show that the applications made get positive responses from users, namely the teachers and parents of students. From the distribution of questionnaires given to users as much as 95% said this application is very effective to use and can help users to control the development of children.